Kirigami-inspired gas sensors for strain-insensitive operation - Jeonhyeong Park; Hyeoncheol Lim; Junwoo Yea; Chaehyun Ryu; Soon In Jung; Runia Jana; Kyung-In Jang; Hohyun Keum; Hoe Joon Kim (Results in Engineering, 2024)
Wearable electronics for the Internet of Things (IoT) have spurred interest in optimizing stretchable substrates, electrodes, and sensing materials. Specifically, wearable gas sensors are valuable for real-time monitoring of hazardous chemicals. For wearable gas sensors, a stable operation under mechanical deformation is required. Here, we introduce strain-insensitive Kirigami-structured gas sensors decorated with titanium dioxide (TiO2) functionalized carbon nanotubes (CNTs) for NO2 sensing. The Kirigami-shaped substrate is used to ensure mechanical stability when stretched. The developed device shows only a 1.3 % change in base resistance under 80 % strain. In addition, the impact of electro-thermal properties at various strain levels is analyzed to aid the understanding of the device's performance. The CNT-TiO2 composite induced alterations in p-n heterojunctions, improving the measurement sensitivity by approximately 250 % compared to a bare CNT sensor. Additionally, the sensors exhibited a 10-fold faster desorption rate due to the enhanced photocatalytic effect of TiO2 under UV exposure. Remarkably, the Kirigami-structured gas sensors maintained stable and repetitive sensing operation even under 80 % strain, which would be enough to be used in various wearable applications.